The Literature of Place
XII, 241 p.
Keywords: This collection of essays discusses writers who have in common their use of the English language. The authors are from all over the world and their subject matter ranges from Shakespeare to Hardy, from Margaret Oliphant to Kazuo Ishiguro and from the Canadian prairies to the Falklands War.